1972
DOI: 10.1139/o72-023
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Procaine with the Nonmyelinated Nerve Axon

Abstract: The interaction of procaine with the nonmyelinated nerve axon from the legs of Homarus americanus was found to produce a conformational change in the lipid structure of the membrane. This conformational change was also observed after treatment of the nerve with acetylcholine bromide but not with any of the following local anesthetics:lidocaine, carbocaine, prilocaine, and nupercaine. It was also found that procaine is a potent inhibitor of acetylcholinesterase whereas the other anesthetics at the same concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1976
1976
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…After the very rapid diffusion of the neurotransmitters across the synaptic cleft to the surface of the postsynaptic membrane, the kinetics of this adsorption into the headgroup region of the bilayer is thus likely to be quite fast, possibly even approaching the time scale of the binding process at the two agonist sites. With regard to equilibrium partitioning, since the closely related compounds acetylcholine and procaine both perturb the mobility of spin labels in membranes (16), the ratio of the magnitude of those effects at equal aqueous concentrations, along with the partition coefficient of procaine (17), provides an order-of-magnitude estimate of that of acetylcholine: a few mol percent in the membrane at millimolar aqueous concentrations, the concentration range in which acetylcholine has also been shown to perturb the surface potential of lecithin monolayer films (18). More generally, it has been shown (19) that charged organic molecules partition much more into membranes than might be expected, largely residing in or near the headgroup region.…”
Section: Discussionmentioning
confidence: 99%
“…After the very rapid diffusion of the neurotransmitters across the synaptic cleft to the surface of the postsynaptic membrane, the kinetics of this adsorption into the headgroup region of the bilayer is thus likely to be quite fast, possibly even approaching the time scale of the binding process at the two agonist sites. With regard to equilibrium partitioning, since the closely related compounds acetylcholine and procaine both perturb the mobility of spin labels in membranes (16), the ratio of the magnitude of those effects at equal aqueous concentrations, along with the partition coefficient of procaine (17), provides an order-of-magnitude estimate of that of acetylcholine: a few mol percent in the membrane at millimolar aqueous concentrations, the concentration range in which acetylcholine has also been shown to perturb the surface potential of lecithin monolayer films (18). More generally, it has been shown (19) that charged organic molecules partition much more into membranes than might be expected, largely residing in or near the headgroup region.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the inclusion of Mg2+ or spermine in the incubation medium was necessary for ribosomemembrane attachment in vitro. Since there may be structural differences between the rough endoplasmic reticulum from brain and liver (Simpkins et al, 1973), it was decided to examine the influence of different concentrations of Mg2+ and spermine on the ribosomemembrane interactions in the two tissues. The results summarized in Table 2 reveal that the omission of both organic and inorganic cations results in a negligible attachment of ribosomes to membranes both in the liver and in the brain homologous systems.…”
Section: Direrential Requirement Of Spermine and Mgz+ For Ribosome-mementioning
confidence: 99%